KONSEP PEMIKIRAN MANAJEMEN PENDIDIKAN ISLAM PERSPEKTIF KH. HASYIM ASY’ARI - Dea Wanda Milarahma Putri; Mila Alvionita; Muhammad Riadhy Harly; Muslim Afandi (Al-mujahidah, 2024)
This article aims to know the concept of education management of K.H. Hasyim Asy'ari through the values developed by K.H. Hashim Asy'ari and identify the tendencies of K.H. Hashim Asy'ari thinking. This research uses qualitative methods with ibrary research. The data used in this study came from journals and books related to the collection of the Qur'an. The data collection method involves collecting data from relevant readings or literature materials according to the research topic. The results of this study show that the concept of Islamic education management K.H. Hasyim Asy'ari with his pesantren in developing the curriculum is almost entirely oriented to the religious curriculum (fiqh oriented) and an education system that maintains tradition in teaching classical books. The uniqueness of KH. Hashim Asy'ari with his pesantren, with its conventional traditional teaching and learning traditions that will face the reality of modernity that demands all kinds of changes, will be able to cause turmoil which if not immediately overcome will threaten the existence of traditional education itself. KH. Hasyim Asy'ari, is one of the figures with the concept of education management thinking that is always related to current conditions. This statement is proven through his works that are always favored by many people and are taken from the essence to solve various educational problems.